MEDICINAL PLANTS OF COLD ARID TRANS-HIMALAYA AS SOURCES OF HEALTH PRODUCTS AND ITS SUSTAINABLE UTILIZATION - Chaurasia, O. P.; Singh, S. B.; Ballabh, B.; Kumar, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plants have always been a source of food, medicine and other necessities of life since time immemorial. Ladakh and Lahaul-Spiti regions of Trans Himalayas are endowed with highly peculiar climate and topographical conditions which have provided a wide range of medicinal, aromatic and other important plants. Even today medicinal plants represent the only source of natural drugs for majority of world’s population. The people of Ladakh and Lahaul-Spiti have their own medical system called “Amchi system of medicine” (Tibetan Medicine) and the practitioners are called Amchis (Superior of all). The widely used medicinal plants from High altitude regions are Aconitum heterophyllum, Dactylorhiza hatagirea, Ephedra gerardiana, Hippophae rhamnoides, Inula racemosa, Podophyllum hexandrum, Rheum webbianum, Rhodiola imbricata, etc. Field Research Laboratory has carried out extensive ethnobotanical survey of the regions and it was observed that medicinal plants were quite useful against high altitude maladies faced by low landers viz.stress, fatigue, loss of appetite, loss of memory, UV radiation, sleep disturbance, frostbite, etc. FRL has developed certain herbal health products using high altitude medicinal plants to improve the working efficiency of low landers deployed in the high altitude cold desert region of India. A Multivitamins Herbal Beverage and Herbal tea have been formulated using high altitude medicinal plants and carried out its biochemical profile, patented and commercialized. The cultivation practices of selected medicinal plants have been standardized for their commercial cultivation, conservation and sustainable utilization.